Sport coaches use of cloud computing: from here to ubiquity - Lyons, K. (International Journal of Computer Science in Sport, 2011)
Cloud computing is providing sport coaches with opportunities to transform their work with athletes. This paper identifies chatacteristics of Cloud computing and discusses sport coaches' use of the 'Cloud'. Examples are presented of this use in the sport of canoeing in Australia. The paper examines some of the risks inherent in a move to Cloud computing whilst acknowledging the dynamic possibilities available from new ways of communicating. The paper concludes with a discussion of the use of iterative 'good enough' approaches to digital repositories.